IT automation versus conventional systems in private universities: TAM and JD-R predictors of academic outcomes in Kupang city - Adrianus Aluman; Sarlianus Poma (STAI Auliaurrasyidin Tembilahan, 2026)
A significant gap exists in quantitative comparative research on IT-based automation versus conventional systems in resource-constrained regional universities, particularly in eastern Indonesia. This study addresses this gap by examining comparative associations between IT-based and conventional systems at private universities in Kupang City, East Nusa Tenggara. Guided by the Technology Acceptance Model (TAM) and Job Demands-Resources (JD-R) theory, a quantitative cross-sectional survey was conducted. A two-stage sampling procedure yielded 215 valid respondents (130 students, 55 lecturers, 30 administrative staff). A 36-item Likert-scale questionnaire demonstrated satisfactory internal consistency (Cronbach's α = .81 to .87). Independent samples t-tests and multiple regression (SPSS v.25) revealed that IT-adopting institutions reported significantly higher student engagement (M = 3.82 vs. 3.31, p < .001), academic productivity (M = 3.91 vs. 3.28, p < .001), and lecturer effectiveness (M = 3.75 vs. 3.29, p = .003). Regression showed perceived usefulness (β = .41, p < .001) and perceived ease of use (β = .29, p = .002) as the strongest productivity predictors (R² = .56). However, IT-adopting institutions also reported higher technostress and reduced face-to-face peer interaction. These findings suggest that a hybrid model may optimize outcomes. This study contributes comparative evidence from an under-researched regional context.